Inclusive education and social exclusion - Maria Luisa Bissoto (Universidade Federal de Santa Maria (UFSM), 2013)
The aim of this paper is critically examining assumptions underlying the Inclusive Education concept, arguing that this can only be effectively considered when understood in a broader context of social inclusion and exclusion. Methodologically, this article relies on international documents and bibliographic references about Inclusive Education, that have been chosen by systematize and characterize different social and educational inclusive practices, encouraging the elaboration of a general overview on this topic. The results of this analysis conclude that it is essential for Inclusive Education that educational institutions review their goals and reasons of social existence. In the concluding remarks it is argued that education is better understood as the act of encouraging and welcoming the efforts of individuals in their attempts to engage in social networking, which sustains life. This includes the acceptance of other reality interpretations and understanding that educational action cannot be restricted by the walls of institutions. It requires the participation of the whole community. Action perspectives likely to promote social inclusion and inclusive education are suggested.